Factors associated with inflammation in preschool children and women of reproductive age: Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) project. (14th June 2017) - Merrill, Rebecca D; Burke, Rachel M; Northrop-Clewes, Christine A; Rayco-Solon, Pura; Flores-Ayala, Rafael; Namaste, Sorrel ML; Serdula, Mary K; Suchdev, Parminder S
ABSTRACT: Background: In many settings, populations experience recurrent exposure to inflammatory agents that catalyze fluctuations in the concentrations of acute-phase proteins and certain micronutrient biomarkers such as C-reactive protein (CRP), α-1-acid glycoprotein (AGP), ferritin, and retinol. Few data are available on the prevalence and predictors of inflammation in diverse settings. Objective: We aimed to assess the relation between inflammation (CRP concentration >5 mg/L or AGP concentration >1 g/L) and covariates, such as demographics, reported illness, and anthropometric status, in preschool children (PSC) (age range: 6–59 mo) and women of reproductive age (WRA) (age range: 15–49 y). Design: Cross-sectional data from the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) project from 29, 765 PSC in 16 surveys and 25, 731 WRA in 10 surveys were used to model bivariable and multivariable relations. Results: The inflammation prevalence was 6.0–40.2% in PSC and 7.9–29.5% in WRA (elevated CRP) and 21.2–64.3% in PSC and 7.1–26.7% in WRA (elevated AGP). In PSC, inflammation was consistently positively associated with recent fever and malaria but not with other recent illnesses. In multivariable models that were adjusted for age, sex, urban or rural residence, and socioeconomic status, elevated AGP was positively associated with stunting (height-for-age z score <−2) in 7 of 10 surveys. In WRA, elevated CRP was positively associated with obesity [body mass index (in kg/m 2 ) ≥30] in 7 of 9 surveys. Other covariates showed inconsistent patterns of association with inflammation. In a pooled analysis of surveys that measured malaria, stunting was associated with elevated AGP but not CRP in PSC, and obesity was associated with both elevated CRP and AGP in WRA. Conclusions: Recent morbidity and abnormal anthropometric status are consistently associated with inflammation across a range of environments, whereas more commonly collected demographic covariates were not. Because of the challenge of defining a general demographic population or environmental profile that is more likely to experience inflammation, inflammatory markers should be measured in surveys to account for their effects.